2002
DOI: 10.1053/jhep.2002.30278
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a reinforced triple course of hepatitis B vaccination in patients transplanted for HBV-related cirrhosis

Abstract: Long-term immunoprophylaxis with anti-HBs immunoglobulins (HBIgH BV reinfection after liver transplantation for HBVrelated cirrhosis is frequent in the absence of immunoprophylaxis and is associated with poor prognosis, resulting from the development of cirrhosis, fibrosing hepatitis, or fulminant hepatitis. 1-2 The introduction of the long-term use of anti-HBs immune globulins (HBIg) has allowed the reduction of graft reinfection to acceptable levels, resulting in survival rates comparable with, or even bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(80 citation statements)
references
References 29 publications
3
75
0
2
Order By: Relevance
“…These results were confirmed with a longer follow-up time [54] and in another study [55]. Conflicting results were reported by Angelico et al using a triple course of hepatitis B vaccination in 17 patients that had undergone transplantation for HBV cirrhosis after cessation of HBIG [56]. Anti-HBs>100 IU/l was observed in only two patients (12%).…”
Section: Discontinuation Of Hbigsupporting
confidence: 53%
“…These results were confirmed with a longer follow-up time [54] and in another study [55]. Conflicting results were reported by Angelico et al using a triple course of hepatitis B vaccination in 17 patients that had undergone transplantation for HBV cirrhosis after cessation of HBIG [56]. Anti-HBs>100 IU/l was observed in only two patients (12%).…”
Section: Discontinuation Of Hbigsupporting
confidence: 53%
“…Sanchez-Fueyo et al 9 have reported that, in selected patients, post-transplantation vaccination with conventional vaccine would allow the discontinuation of lifelong HBIg treatment. However, Angelico et al 10 did not find a favorable results from reinforced vaccination in OLT patients, although some of their patients developed anti-HBs due to this approach. It is an open debate as to why patients in the Spanish group (reported by Sanchez-Fueyo et at.…”
Section: Discussionmentioning
confidence: 92%
“…Studies of hepatitis B vaccination as an alternative to long-term HBIG in LT recipients have shown that successful hepatitis B vaccination and discontinuation of HBIG are feasible only in a small group of selected patients; however, the optimal vaccine protocol has not been established [25,26]. …”
Section: Prevention Of Hbv Recurrencementioning
confidence: 99%